Effects of Amitriptyline on the Lipid Profile, Antioxidant, and Hormones of the first filial generation of Wistar Rats. (Journal of Medical Sciences, 2024)
Aim: This study investigated the effect of amitriptyline on the first filial generation of female Wistar rats by analyzing the anti-oxidant levels in serum and tissue, lipid profile, and reproductive hormones. Methodology: Twenty-five adults female Wistar rats (12 weeks) weighing between 150 and 180g were grouped into five (n=5). Group 1 (control) received 0.2 ml/kg of normal saline solution 28 days before and throughout the gestational period, group 2 and 3 received (5 and 10mg/kg) of amitriptyline respectively, 28 days before and throughout the gestation period; Group 4 and 5 (5 and 10mg/kg) of amitriptyline respectively for 28 days before the gestational period alone. After delivering, five female offspring rats from each group were allowed to grow naturally till puberty (12 weeks). Blood samples collected were analyzed for the level of GPx, Total cholesterol, Triglycerides, Low-density lipoprotein, High-density lipoprotein, estradiol, progesterone, prolactin, superoxide dismutase (SOD), Catalase (CAT), and Malondialdehyde (MDA) were assayed in the tissue homogenate and serum of the offspring. Results: Amitriptyline increases the MDA level of the offspring of the experimental animal, and decreases the level of SOD, CAT, and Estradiol. Conclusion: Amitriptyline induces oxidative stress, sexual dysfunction, and infertility in the F1 generation of Wistar rats.